All grown up - Attenberg, Jami (Houghton Mifflin Harcourt, 2017)
Hiding the truth about her unhappiness and struggles with anxiety from everyone including her family, best friend, and therapist, Andrea Bern joins her loved ones in a reevaluation of family strength in the wake of her newborn niece's heartbreaking ailment.